Downsizing effect of a modular radial head prosthesis on the lateral collateral ligament of the elbow: A cadaveric study. (December 2020) - Hatta, Taku; Shinagawa, Kiyotsugu; Kawakami, Jun; Yamamoto, Nobuyuki; Kitada, Masaaki; Itoi, Eiji
Abstract: Background: It remains unclear how the head and stem diameters for the radial head prosthesis could affect mechanical properties of the lateral collateral ligament measured by strain changes during elbow and forearm motions. Methods: Eight cadaveric specimens were secured to the device, which allows elbow flexion-extension and forearm pro-supination. Using six different implant combinations comprising 2 sizes for the head (long- and short-axis of the native head) and 3 sizes for the stem (press-fit, −1 mm, and −2 mm downsizing), prostheses were attached via the posterior approach. A differential variable reluctance transducer placed on the central portion of the radial collateral ligament were used for strain measurement with elbow flexion at 0°, 30°, 60°, and 90°. At each position, the strain patterns with the forearm in the neutral and 45° pro-supination positions were also assessed. Findings: Specimens implanted with long-axis head component showed greater increases in the ligament strain during elbow flexion than intact specimens or those implanted with short-axis head. Compared to press-fit stem, implants with downsizing to −1 mm approximated strain patterns during pro-supination with elbow extension to intact condition. Interpretation: Morphologic variation of the head and stem components in radial head prostheses led to altered strain patterns in the lateral collateral ligament during elbow and forearm motions. A short-axis head component can be used to prevent excessive strain changes after the prosthesis application. Downsizing of the stem component might be an option for approximating the biomechanics at the radiocapitellar joint during forearm rotation to the intact elbow. Highlights: Strain changes in the radiocapitellar joint after modular radial head prosthesis were assessed. Morphologic variation of implants altered strain patterns of the lateral collateral ligament. Prosthesis with short-axis head and downsized stem approximated strain patterns to intact elbow.